-enhanced zinc aluminate microwave dielectric ceramics for electronic packaging to thermally match printed circuit boards - Liyuan Huang; Yuanxun Li; Yanfeng Shang; Chuming Li; Xinyan Liu; Longyuan Zhao; Fuyu Li (Journal of Advanced Dielectrics)
With the rapid development of electronic integration technology, highly integrated chips are in urgent need of packaging materials that are thermally matched to printed circuit boards. Here, [Formula: see text]CoxAl2O4 (ZCAO, x= 0.00–0.20) ceramics are synthesized using the solid-state reaction method. The phase composition, microstructure, microwave dielectric properties and CTE of [Formula: see text] in the ZnAl2O4 ceramic substituted by [Formula: see text] are systematically revealed. An appropriate amount of [Formula: see text] substitution promotes a more homogeneous grain growth to form a dense microstructure. The average grain size, bulk density and relative density of ZCAO ([Formula: see text]) ceramic are 1.59[Formula: see text][Formula: see text]m, 4.472[Formula: see text]g/cm3 and 97.4%, respectively. The optimal microwave dielectric properties ([Formula: see text], [Formula: see text],701[Formula: see text]GHz, [Formula: see text][Formula: see text]ppm/∘C) of the ZCAO ([Formula: see text]) ceramic sintered at 1450∘C are achieved. More importantly, the ZCAO (x = 0.10) possesses a CTE = 11.59[Formula: see text]ppm/∘C that is nearly thermally matched to the printed circuit boards (PCB, CTEPCB = 12[Formula: see text]ppm/∘C). This ceramic has great potential for application in the electronic packaging of PCB devices.